Context counts: Solitary drinking explains the association between depressive symptoms and alcohol-related problems in undergraduates. (March 2015) - Keough, Matthew T.; O'Connor, Roisin M.; Sherry, Simon B.; Stewart, Sherry H.
Abstract: Introduction: According to theory, depressed individuals self-medicate their negative affect with alcohol. Due to isolation and interpersonal difficulties, undergraduates with elevated depressive symptoms may do much of their drinking alone and/or in intimate contexts (e.g., with family or romantic partners) rather than at normative social events (e.g., parties). Evidence suggests drinking in these contexts leads to heavy use and alcohol-related problems. Accordingly, context may be an explanatory mechanism linking depressive symptoms to problematic drinking. This pathway remains understudied in the literature. Our study aimed to examine solitary and intimate drinking as distinct mediators of the depression–problematic drinking association. We hypothesized that depressive symptoms would be positively associated with solitary and intimate drinking which in turn would be associated with elevated alcohol use and related problems. Methods: Undergraduates ( N = 295; 72% women) completed online self-reports. Results: Consistent with hypotheses, path analyses supported depressive symptoms as a positive predictor of solitary drinking, which in turn was a positive predictor of alcohol-related problems, but not of alcohol use. Counter to hypotheses, depressive symptoms were unrelated to intimate drinking. Interestingly, depressive symptoms were negatively associated with drinking at parties, which in turn led to reduced risk for elevated alcohol use and related problems. Conclusions: Our results shed new light on the depression pathway to problematic drinking in undergraduates by considering the role of drinking context. Our findings suggest undergraduates with elevated depressive symptoms are at risk for potentially problematic drinking because they are drinking alone. Solitary drinking represents a malleable target for clinical interventions aimed at reducing risky depression-related alcohol use. Highlights: We test the mediating roles of drinking contexts in depression-related alcohol use. High-risk pathway via solitary drinking in those with elevated depressive symptoms. Low-risk pathway via drinking at parties in those high in depressive symptoms. Context may be a malleable target for treatments for depression-related drinking.